Volumetric properties, viscosities and refractive indices of 3-diethylamino propylamine (DEAPA) + water system from 293.15 K to 343.15 K. (January 2020) - Philip, Firuz A.; Nath, Devjyoti; Sibilla, Kevin; Henni, Amr
Graphical abstract: Highlights: Density, viscosity and refractive index of 3-(Diethylamino) propylamine were reported. Excess properties of the aqueous DEAPA solutions were calculated. Activation energies and entropies for viscous flow were estimated. Viscosity data suggested the possible formation of stable complex. Abstract: In this study, the physiochemical and transport properties of 3-(Diethylamino) propylamine (DEAPA) + water system were investigated. The densities and refractive indices of aqueous DEAPA solutions were measured at a range of temperatures from 293.15 K to 343.15 K, and at a pressure p = 95.1 (±0.8) kPa. The viscosities of the aqueous DEAPA were also measured from T = 298.15 K to 333.15 K. The excess properties of aqueous DEAPA solutions were calculated based on the experimental results. In addition, the activation energies and entropies for viscous flow were estimated from the viscosity data. The Redlich–Kister equation was used to correlate all excess properties. Based on volumetric data, DEAPA could not be described as structure breaker or structure maker, however, the nature of changes of viscosity against concentration (S-shaped) suggested the formation of stable complex.